2008
DOI: 10.1016/j.cognition.2007.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Memory for “mean” over “nice”: The influence of threat on children’s face memory

Abstract: Adults remember faces of threatening over non-threatening individuals. This memory advantage could be indicative of a system rooted deeply in cognitive evolution to track and remember individuals who have been harmful in the past and therefore might be harmful again. Conversely, adults may have learned through experience that it pays to be vigilant. In the present research, we investigated whether attention to threatening individuals is privileged in young children's face memory. In Experiment 1, preschool-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 25 publications
6
69
3
1
Order By: Relevance
“…In support of this theory, Kinzler and Shutts (2008) found that 4 year olds showed enhanced recognition for individuals who had committed a harmful action relative to helpful individuals. Further, 4 year olds did not show increased recognition for recipients of harmful acts over recipients of helpful acts, suggesting that such differences in the first experiment were not driven by generally better memory for negative events but by the motivation to detect and remember potentially threatening individuals.…”
Section: Extracting Valence Information From Social Behavioursmentioning
confidence: 59%
See 1 more Smart Citation
“…In support of this theory, Kinzler and Shutts (2008) found that 4 year olds showed enhanced recognition for individuals who had committed a harmful action relative to helpful individuals. Further, 4 year olds did not show increased recognition for recipients of harmful acts over recipients of helpful acts, suggesting that such differences in the first experiment were not driven by generally better memory for negative events but by the motivation to detect and remember potentially threatening individuals.…”
Section: Extracting Valence Information From Social Behavioursmentioning
confidence: 59%
“…Indeed, faces seem to hold a special status in infant memory-6-month-olds' memory for photographs of faces are more durable than for abstract black and white patterns, for example (2 weeks versus 48 hours respectively, Fagan, 1973). Furthermore, research we will discuss in more detail later shows that other factors, such as the actions of the individual concerned, can affect face recognition at least in 4-year-olds (Kinzler & Shutts, 2008).…”
Section: Tracking Individuals-infants Ability To Recognise Facesmentioning
confidence: 94%
“…When each object is presented in comparison to a neutral object, infants engage with the neutral object over the negative object, yet they treat positive and neutral objects the same (Hornik, Risenhoover, & Gunnar, 1987;Mumme & Fernald, 2003). By preschool age, children's patterns of visual search reflect an advantage for monitoring faces displaying negative over neutral or positive expressions (LoBue, 2009), and children similarly exhibit better memory for individuals who are described as mean, rather than nice (Baltazar et al, 2012;Kinzler & Shutts, 2008). Enhanced attention to and memory for negative events may serve a protective function in guarding children against harmful future situations.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the negativity bias, past research provides evidence of children's and adults' heightened attention to, and memory for, negative social information (Baltazar et al, 2012;Baumeister et al, 2001;Kinzler & Shutts, 2008;LoBue, 2009;Rozin & Royzman, 2001). Beginning as early as infancy, children preferentially attend to negative over positive social information (see Vaish et al, 2008, for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than being influenced by self-concept, these memories are affected by different pressures, namely the adaptive utility of remembering that someone has done something negative so that they can be avoided in the future (e.g., Kinzler & Shutts, 2008). This is particularly interesting because it means that memory for the same actions may be very different depending on whether they are carried out by oneself or someone else.…”
Section: Negativity In Memory Of Othersmentioning
confidence: 99%